The subversion of the image: the doubleness and the the unsharpness in Zbigniew Libera's 'La Vue´ - Luczak, Dorota (Revelar: Journal of Photography and Image Studies, 2018)
The subject matter of the article is the series ´La Vue´ by Zbigniew Libera in wich photograph itself and landscape view become objects of the play with language and image convetions. The reference for this play is composed from this writing of Raymond Roussel (1877-1933), and is conceptualized strategy of doublness. [...]